Analisis Pengaruh Tingkat Suku Bunga Deposito Terhadap Jumlah Nasabah Pada PT. Bank Rakyat Indonesia (Persero) Tbk Unit Pangli (International Forum of Researchers and Lecturers, 2023)
This research aims to analyze the effect of interest rates on the number of customers at Bank Rakyat Indonesia Pangli Unit. The information used in this examination includes savings rates and number of customers for the last three years, from 2019 to 2021. The analytical method applied in this exploration is comparative descriptive with primary data by utilizing important information obtained directly from the object of the examination. The consequences of this research show that there is a relationship between deposit interest rates and the number of customers at Bank Rakyat Indonesia Pangli Unit.